What Is the Impact of Heatwaves on European Viticulture? A Modelling Assessment - Fraga, Helder (2020)
Extreme heat events or heatwaves can be particularly harmful to grapevines, posing a major challenge to winegrowers in Europe. The present study is focused on the application of the crop model STICS to assess the potential impacts of heatwaves over some of the most renowned winemaking regions in Europe. For this purpose, STICS was applied to grapevines, using highresolution weather, soil and terrain datasets from 1986 to 2015. To assess the impact of heatwaves, the weather dataset was artificially modified, generating periods with anomalously high temperatures (+5 °C), at specific onset dates and with specific episode durations (from five to nine days). The model was then run with this modified weather dataset, and the results were compared to the original unmodified runs. The results show that heatwaves can have a very strong impact on grapevine yields. However, these impacts strongly depend on the onset dates and duration of the heatwaves. The highest negative impacts may result in a decrease in the yield by up to −35% in some regions. The results show that regions with a peak vulnerability on 1 August will be more negatively impacted than other regions. Furthermore, the geographical representation of yield reduction hints at a latitudinal gradient in the heatwave impact, indicating stronger reductions in the cooler regions of Central Europe than in the warmer regions of Southern Europe. Despite some uncertainties inherent to the current modelling assessment, the present study highlights the negative impacts of heatwaves on viticultural yields in Europe, which is critical information for stakeholders within the winemaking sector for planning suitable adaptation measures